2018
DOI: 10.1016/j.pediatrneurol.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of Niemann-Pick Type C1 Disease With Intrathecal 2-Hydroxypropyl-β-Cyclodextrin

Abstract: These trajectories are not consistent with the typical trajectory of the disease and suggest that intrathecal 2-hydoxypropyl-β-cyclodextrin has stabilized the disease over an extended period of time, supporting the current phase 2/3 controlled registration trial with VTS-270.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Importantly, HP-BCD has been extensively reported to be safe for human use as an oral, topical, and parenteral agent ( 26 29 ). In addition, a phase 1/2a clinical trial designed to test the safety and effectiveness of intrathecal injections of HP-BCD for the treatment of NPCD patients was recently successfully completed ( 27 , 28 ). Therefore, the data presented in this study provide substantial support for the evaluation of HP-BCD as an antiretroviral drug potentially able to reduce viral replication ( 29 32 ) and control HIV-associated chronic immune activation that aggravates HIV comorbidities and AIDS progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, HP-BCD has been extensively reported to be safe for human use as an oral, topical, and parenteral agent ( 26 29 ). In addition, a phase 1/2a clinical trial designed to test the safety and effectiveness of intrathecal injections of HP-BCD for the treatment of NPCD patients was recently successfully completed ( 27 , 28 ). Therefore, the data presented in this study provide substantial support for the evaluation of HP-BCD as an antiretroviral drug potentially able to reduce viral replication ( 29 32 ) and control HIV-associated chronic immune activation that aggravates HIV comorbidities and AIDS progression.…”
Section: Discussionmentioning
confidence: 99%
“…2-Hydroxypropyl-beta-cyclodextrin (HP-BCD) is a cholesterol-sequestering drug, which is being used in humans for several pharmaceutical applications and has also been tested in human clinical trials of Niemann Pieck C disease (NPCD), with a safe profile ( 26 28 ). Importantly, this agent has been extensively demonstrated to inactivate HIV in vitro , including ART-resistant virus ( 29 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a report of the use of cyclodextrin for the delivery of VTS-270 for treatment of Niemann-Pick disease type C (NPC) (40). NPC is a lethal, autosomal recessive, lysosomal storage that leads to progressive accumulation of unesterified cholesterol and other lipids in the central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 99%
“…NPC is a lethal, autosomal recessive, lysosomal storage that leads to progressive accumulation of unesterified cholesterol and other lipids in the central nervous system (CNS). The National Institute of Health (NIH) Therapeutics for Rare and Neglected Diseases (TRND) program is developing cyclodextrin for the treatment of patients with Niemann-Pick disease type C1 (NPC1) to slow progression of symptoms of the disease (40).…”
Section: Discussionmentioning
confidence: 99%
“…One of these trials showed restoration of neuronal cholesterol homoeostasis and a decrease in CNS pathology in children less than 18 months of age [89]. In three children aged from 30 to 36 months, HPβCD improved scores on the cognitive level, swallowing ability, fine motor skills, and balance/gait [90]. Another trial with 14 participants of a wider scale of ages, from 4 to 23 years, confirmed that there is an overall slowing of the progression of the disease upon intrathecal administration of HPβCD (at doses of up to 600 to 1200 mg/month, according to the tolerance of each patient); the patients were medicated for three years [91].…”
Section: Hpβcd An Orphan Drug For Niemann-pick Disease Type Cmentioning
confidence: 99%